Enhancing Students’ Learning through Classroom-Based Assessment in Secondary School Science and Technology Education - Adhikari , Yuba R. (Education Review Journal, 2025)
Assessment plays a crucial role in the curriculum. Among its various types, Classroom-Based Assessment (CBA) serves as a formative approach that supports students’ learning by providing feedback and promoting active participation in the learning process. In secondary school Science and Technology subjects, CBA helps educators identify students’ strengths and weaknesses, analyze reasons for students’ confusion, and allow for timely instructional adjustment. This study explores the role of CBA in enhancing students’ learning outcomes in the secondary school Science and Technology subject. This study also reflects the role of CBA in improving student learning outcomes, focusing on strategies such as formative and internal students’ participation, practical and project work assessment, peer assessments, and self-assessments. A qualitative approach is employed for data collection and analysis. This research studies how various CBA strategies influence teaching and learning practices, student engagement, and conceptual understanding. The findings reveal that well-structured systemic formative and internal assessments, providing timely feedback, promote deeper understanding, critical thinking, and student autonomy in learning. Learner-centered assessment approaches significantly contribute to achieving learning competencies and learning outcomes, as well as scientific inquiry and science process skills. However, challenges such as teacher preparedness, a large number of students, the overload of classroom periods, and time constraints hamper its full implementation. The study recommends professional development for teachers and the integration of digital tools to enhance CBA effectively. It highlights the importance of policy-level support and teacher professional development to strengthen CBA.